The night before New Year's - Wing, Natasha; Wummer, Amy (New York : Grosset & Dunlap, 2009)
In this version of Clement Moores' classic poem, a brother and sister struggle to stay awake until midnight to ring in the new year.
Keywords: New Year -- Juvenile poetry; Children's poetry, American; New Year -- Poetry; Family life -- Poetry; Narrative poetry; American poetry